Iranian teachers' reflective teaching practice in relation to self-efficacy perceptions: investigating teachers' discipline. Issue 3 (3rd May 2020) - Kurosh, Shabnam; Yousefi, Mohammad Hossein; Kashef, Seyyed Hossein
ABSTRACT: Although there have been several studies investigating the role of self-efficacy and reflective teaching in the literature, no research, to date, investigated teachers' reflective practice teaching from different academic disciplines. The present study was a survey research that attempted to bridge this gap. For this purpose, a total of 70 teachers from the hard science, soft science and EFL disciplines from both private and public universities in Iran took part in this study. All teachers had over 10 years of teaching experience, with the majority being PhD holders. The Teacher Efficacy Scale (TES) and teacher reflection questionnaire were used to investigate teachers' senses of self-efficacy and reflective practice, respectively. Results of Pearson correlation coefficients revealed that except for the ELT teachers, other discipline teachers' self-efficacy perceptions were not related to their reflectivity. The present study has a number of implications for teacher development and in-service teacher education programs.